2011
DOI: 10.3945/jn.111.140053
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Transporter Genes Are Coordinately Expressed in Men and Women Independently of Dietary or Plasma Zinc

Abstract: The zinc transporter (ZnT; SLC30) and Zrt- and Irt-like protein (Zip, SLC39) zinc transporter families are integral to the maintenance of intracellular zinc concentrations. Few studies have examined the expression patterns of zinc transporter genes in human primary tissues. This study investigated the expression levels of a range of zinc transporter mRNA in the peripheral blood mononuclear cells of healthy men and women (n = 40) using quantitative real-time PCR. It also explored the relationships among zinc tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
4
25
0
2
Order By: Relevance
“…The primary finding is a significant upregulation of MT-2A gene expression within two days of zinc supplementation, in the absence of significant change in plasma zinc concentration. Our previous report suggests coordination among components of cellular zinc homeostasis (Foster et al 2011), and the current findings extend these observations by demonstrating numerous relationships between the expression of zinc transporter and MT genes at baseline and during zinc supplementation. Specifically, the use of multiple regression models showed that the difference in MT-2A gene expression over the trial period was determined by changes in the expression of zinc transporter genes.…”
Section: Discussionsupporting
confidence: 69%
“…The primary finding is a significant upregulation of MT-2A gene expression within two days of zinc supplementation, in the absence of significant change in plasma zinc concentration. Our previous report suggests coordination among components of cellular zinc homeostasis (Foster et al 2011), and the current findings extend these observations by demonstrating numerous relationships between the expression of zinc transporter and MT genes at baseline and during zinc supplementation. Specifically, the use of multiple regression models showed that the difference in MT-2A gene expression over the trial period was determined by changes in the expression of zinc transporter genes.…”
Section: Discussionsupporting
confidence: 69%
“…41, 42, 43 Expression of ZnT-1 is induced by high zinc concentrations in LNCaP and PC-3 human prostate cancer cells, 44 consistent with its putative role as a zinc export protein. Indeed, one in vitro study demonstrated that induction of ZNT1 gene transcription is mediated by the binding of the metal-specific transcription factor MTF-1 to two metal response elements (MRE) in the ZnT-1 promoter.…”
Section: Zinc Transportmentioning
confidence: 70%
“…To date, 14 mammalian ZIP members have been identified; 43 however, only ZIP1, ZIP2, ZIP3, and ZIP4 have been shown to be localized to the plasma membrane and therefore, participate in importing zinc from extracellular fluid. 41, 4853 ZIP1 is important for the extraction of zinc from circulation as the primary source of cellular zinc, whereas ZIP2 and ZIP3 seem to be important for the retention of zinc in the cellular compartment.…”
Section: Zinc Transportmentioning
confidence: 99%
“…Plasma zinc in group A increased by 31 µg/dL, while in group B, it decreased by 25 µg/dL. As ZIP1 (importer) and ZnT1 (exporter) are among the most abundantly expressed zinc transporters [24,29] and their expressions were down-regulated and up-regulated, respectively, after short periods of zinc supplementation [6,17], we selected these markers for evaluation.…”
Section: Discussionmentioning
confidence: 99%